Reflections on Current Trends and Predictions for Commercial Law Libraries. (June 2019) - Wiggins, Samuel
Abstract: This article, written by Samuel Wiggins, examines current trends within commercial law firm libraries, and considers how those trends might continue over the next five to ten years. Areas considered include legal technology, the future of the library space, the role of the professional body, training, and the relationship between traditional librarianship and knowledge management.